2017
DOI: 10.1002/cncr.30977
|View full text |Cite
|
Sign up to set email alerts
|

Trends in major upper abdominal surgery for cancer in octogenarians: Has there been a change in patient selection?

Abstract: BACKGROUND:Although there is a general perception that, as the older population grows in number, more are undergoing surgery, there are few data on trends in major resections for cancer and short-term outcomes in this group. METHODS: The Nationwide Inpatient Sample was (NIS) used to estimate the national trends of major upper abdominal resections (esophagus, stomach, liver, pancreas) for cancer in octogenarians (aged 80 years) from 2001 to 2011. Resection rates performed per year were incidence-adjusted within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…3 Postoperative morbidity and mortality after liver resection for primary and secondary liver tumours tend to increase as older patients are accompanied with more comorbidities and frailty as well as aging of the liver. [4][5][6] During preoperative multidisciplinary treatment meetings, preoperative optimization becomes more important to decrease the negative impact of these comorbidities of patients who face liver resection for primary and secondary liver tumours. 7 To date, age has been seen as a risk factor for complications and mortality in liver surgery but it remains unclear to what extent other patient demographics, disease burden or operative characteristics play a role.…”
Section: Introductionmentioning
confidence: 99%
“…3 Postoperative morbidity and mortality after liver resection for primary and secondary liver tumours tend to increase as older patients are accompanied with more comorbidities and frailty as well as aging of the liver. [4][5][6] During preoperative multidisciplinary treatment meetings, preoperative optimization becomes more important to decrease the negative impact of these comorbidities of patients who face liver resection for primary and secondary liver tumours. 7 To date, age has been seen as a risk factor for complications and mortality in liver surgery but it remains unclear to what extent other patient demographics, disease burden or operative characteristics play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities are a risk factor for occurrence of postoperative morbidity and mortality due to a decrease of functional reserve [6][7][8]. Several studies from various surgical fields on major surgical procedures in elderly patients have shown higher morbidity and mortality rates [3,[9][10][11][12]. Clinical studies have also shown that higher age and additional comorbidities of a patient can be a reason to refrain from major surgical procedures as occurrence of perioperative complications can decrease quality of life and long-term outcomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, the proportion of population who were 80 years or older (octogenarians) increased from 3.2% in 2000 to 4.6% in 2019 [2]. Major surgical procedures were described to be performed more often in octogenarians after the year 2000 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A 2007 landmark study by Bilimoria et al, utilizing data from the National Cancer Database (NCDB) (1995–2004), reported underutilization of surgical resection among patients with PC, potentially due to outdated and nihilistic views of the disease 6,7 . This hesitancy toward pancreatectomy is magnified in the elderly, which negatively impacts survival 8–10 . Our group recently reported that approximately half of octogenarians did not receive any treatment for localized pancreatic head cancer, and only 11% received chemotherapy in addition to pancreaticoduodenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This hesitancy toward pancreatectomy is magnified in the elderly, which negatively impacts survival. [8][9][10] Our group recently reported that approximately half of octogenarians did not receive any treatment for localized pancreatic head cancer, and only 11% received chemotherapy in addition to pancreaticoduodenectomy.…”
mentioning
confidence: 99%